'Using a Blacksmith's Hammer to Crush a Fly': Jallianwala Bagh, Public Order and Popular Protests in late Colonial India. (January 2020) - Wani, Javed Iqbal
This article reconstructs the unfolding of events in India in March–April 1919 that led to the Jallianwala Bagh massacre. It evaluates the circumstances and the administrative and military response from a legal history perspective. It argues that the Jallianwala Bagh massacre was not a unique event but culminated colonial rage against a broader anti-colonial mobilisation.